Exchange rate pass-through to trade prices: the role of non-linearities and asymmetries - Matthieu Bussière (European Central Bank (ECB), 2007)
A standard assumption in the empirical literature is that exchange rate pass-through is both linear and symmetric, implying that (a) large and small exchange rate changes and (b) appreciations and depreciations have an effect of the same magnitude, proportionally. This paper tests these assumptions for export and import prices in the G7 economies. It focuses on non-linearities in the reaction of profit margins to exchange rate movements, which may arise from the presence of price rigidities and switching costs. To this end, nonlinearities are characterised by augmenting a standard linear model with polynomial functions of the exchange rate and with interactive dummy variables. The presence of such non-linearities is confirmed by formal statistical tests. Overall, the results suggest that non-linearities and asymmetries in the exchange rate pass-through cannot be ignored, especially on the export side, although their magnitude varies noticeably across countries.
Keywords: C22; C51; F14; F31; 330; Exchange Rate Pass-Through; Non-linear Model; Trade Prices; Exchange Rate Pass-Through; Außenhandelspreis; G7-Staaten